P29 Medicine prescribing across primary, secondary and tertiary care interfaces in paediatrics: a retrospective cohort study. Issue 5 (20th April 2022) - Birring, Caprice; Huynh, Trinh; Hayes, Patricia; Sadowska-Koszela, Agnieszka; Christiansen, Nanna; Rashed, Asia N
Abstract : Aim: Shared care agreements, commissioned by local clinical commissioning groups, are formal agreements that set out prescribing arrangements to provide a safe and cost-effective service that covers the prescribing requirements and to allow for the continued involvement of a hospital consultant alongside the provision of care in primary care settings. 1–3 However, primary care prescribers have often expressed hesitancy to accept responsibility for prescribing in paediatrics, leaving secondary and tertiary care providers to prescribe these medications instead, 1 resulting in inappropriate pressures on hospital pharmacies and often leaves families with difficulties in securing ongoing supply. This study aimed to investigate the volume, cost and type of hospital outpatient paediatric prescribing associated with items for which prescribing responsibility could be transferred to primary care. As well as to identify whether the current shared care agreements; traffic light rating (TLR) system and associated guidelines, encompass these medications. Method: A retrospective cohort study, involving descriptive and inferential statistical analysis, was conducted on prescription items prescribed and dispensed for paediatric patients. Prescriptions were identified by dispensary staff over a six-month period (October 2019-March 2020), at one tertiary care level hospital in southeast London. The prescription items were classified according to the TLR system defined in the South East London Joint Medicines formulary 4 as red (specialist/hospital prescribing only); amber-1 (primary care initiation after a recommendation from a specialist); amber-2 (specialist initiation followed by maintenance prescribing in primary care); amber-3 (specialist initiation with ongoing monitoring using shared care agreement documentation); green (specialist or non-specialist prescribing). Data were analysed using Statistical Package for the Social Sciences (IBM SPSS) Software (V27). Results: In total 217 prescribed items prescribed and dispensed for 35 children were included in the study, and all of them had the potential to be prescribed in primary care. Of these, 93.1% (202/217) were rated 'green' with most of them prescribed for children aged 6-11 years (32.2%, 65/202). Only 3.2% (7/217) items had an 'amber-3' rating and required shared care agreements to initiate prescribing in primary care, many of them (85.7%, 6/7) had shared care agreements in place, assigned for their use in primary care. Only one item from the 'amber-3' category (melatonin 2 mg modified-relates tablets) had no shared agreement in place. None of the included items was classified as 'red'. The highest volume of prescribing was for paediatric renal (62.2%, 135/217). The total cost incurred to the hospital for all items included in the study was £35, 331. Conclusion: There is still hesitancy among general practitioners to prescribe medications for paediatrics in primary care that they can be clinically responsible for despite the emergence of new guidelines and resources to support primary care in taking on prescribing. This has a significant impact on hospital pharmacies both in terms of activity and finance and it is also making it more complex for arranging medication supplies. If those medicines were prescribed appropriately, considerable cost savings could occur in secondary/tertiary care which could be used to provide other important specialist paediatric services. References: NHS England. Responsibility for prescribing between primary & secondary/tertiary care. 2018. Available at: https://www.england.nhs.uk/wp-content/uploads/2018/03/responsibility-prescribing-between-primary-secondary-care-v2.pdf (accessed 29 Jul 2021). Terry D, Sinclair A. Prescribing for children at the interfaces of care. Archives of Disease in Childhood - Education and Practice 2012;97 :152–156. British Medical Association. Prescribing in General Practice. Available at: https://www.bma.org.uk/advice-and-support/gp-practices/prescribing/prescribing-in-general-practice (accessed 29 Jul 2021). South East London Area Prescribing Committee. South East London Joint Medicines Formulary. Available at: http://www.selondonjointmedicinesformulary.nhs.uk/default.asp (accessed 29 Jul 2021).